Waste palm leaves-based hydrochar support catalytic esterification of palm fatty acid distillate - Aliyu, Muhammad; Rashid, Umer; Wan Ab Karim Ghani, Wan Azlina; Mohd Salleh, Mohamad Amran; Hazmi, Balkis; Alharthi, Fahad A.; Antunes, Elsa; Yu, Jianglong (Springer, 2024)
Heterogeneous acid catalysis provides a sustainable and cost-effective replacement to homogeneous catalysts, as it is easily accessible and reusable. In this research, biodiesel was synthesized from palm fatty acid distillate (PFAD) by way of esterification utilizing a heterogeneous acid catalyst composed of CuO/WPLAHC-S, which was derived from waste palm leaves-based hydrochar. The catalyst was characterized using TGA, XRD, FESEM, EDX, BET, FT-IR, Raman, and acid density. The synthesized catalyst was found to have remarkable stability during the thermal test. The BET surface area, pore volume, and pore width of the synthesized catalyst were measured at 118.47 m2/g, 0.05 cm3/g, and 8.15 nm, respectively. The significant acidity density (18.57 mmol/g) facilitated the simultaneous esterification process. The investigation found that the copper-doped activated hydrochar, treated with sulfuric acid, exhibited excellent catalytic activity. A high yield of 98.34% fatty acid methyl ester (FAME) was achieved under mild conditions with the use of a catalyst concentration of 2 wt.%, a methanol-to-PFAD molar ratio of 15:1, and a reaction temperature of 80 °C for a duration of 3 h. For statistical analysis, one-way ANOVA was applied to verify the experimental data set for PFAD esterification optimization parameters by predetermining a 95% confidence interval. All of the esterification parameters met the expectation of a p-value less than 0.05 indicating its significant impact on FAME production. The catalyst exhibited excellent performance by maintaining a FAME yield of over 90% after four reaction cycles without requiring reactivation. The study demonstrates the efficacy of CuO/WPLAHC-S as a promising acid catalyst derived from waste palm leaves-based hydrochar for biodiesel production from PFAD. Graphical Abstract: (Figure presented.)